Synthesis, characterization and investigation of electrochemical and spectroelectrochemical properties of peripherally and non-peripherally tetra 2-methyl-5-benzothiazole substituted nickel(II), copper(II) and cobalt(II) phthalocyanines - KOCA, ATIF (ELSEVIER SCIENCE SA, 2017)
In this study novel tetra 2-methyl-5-benzothiazole substituted peripherally nickel(II) (6), copper(II) (8), cobalt(II) (10) and non-peripherally nickel(II) (7), copper(II) (9), cobalt(II) (11) phthalocyanines were synthesized. These novel compounds were characterized by a combination of FT-IR, H-1 NMR and UVvis and MALDI-TOF mass spectroscopic techniques. Electrochemical measurements gave well illustrated redox responses for the Pc ring and/or metal center of the complexes. While MPc bearing redox inactive metal centers underwent [(MPc-2)-Pc-II]/[(MPc-3)-Pc-II](1-), [(MPc-3)-Pc-II](1-)/[M(II)Pc(-)4](2-), [(MPc-4)-Pc-II](2-)/[(MPc-5)-Pc-II](3-) and [(MPc-2)-Pc-II](1-)/[(MPc-1)-Pc-II](1+) redox couples. (CoPc)-Pc-II illustrated [(CoPc-2)-Pc-II]/[(CoPc-2)-Pc-I](1-), [(CoPc-2)-Pc-I](1-)/[(CoPc-3)-Pc-I](2-), [(CoPc-3)-Pc-I](2-)/[(CoPc-4)-Pc-I](3-) and [(CoPc-2)-Pc-II]/[(CoPc-2)-Pc-II](1+) redox couples respectively during reduction and oxidation processes respectively. Position of the substituents altered the chemical and electrochemical reversibility of the redox processes. While the substituents were non-peripheral position, the complexes aggregated and both of the redox processes of the aggregated and nonaggregated species were observed, incorporation of the substituents to peripheral position decreased aggregations of the complexes, therefore MPcs substituted at peripheral positions illustrated well resolved reversible redox reactions. In situ spectroelectrochemical results illustrated that electrogenerated MPc species had distinct color differences.
Keywords: Phthalocyanine; Benzothiazolol; lectrochemistry; Spectroelectrochemistry; BENZOTHIAZOLE; MANGANESE; BULKY; FILMS; IRON